Exploring effects of self‐management on glycemic control using a modified information–motivation–behavioral skills model in type 2 diabetes mellitus patients in Shanghai, China: A cross‐sectional study: 中国上海市2型糖尿病患者利用改进的信息‐动机‐行为技巧模型对血糖控制的自我管理的作用机制探索:一项横断面研究. Issue 9 (23rd March 2018) - Chen, Qi; Wang, Huwen; Wang, Yichen; Wang, Zezhou; Zhao, Daijun; Cai, Yong
Abstract: Background: The original information–motivation–behavioral skills (IMB) model has been verified in type 2 diabetes mellitus (T2DM) patients, but the effects of the model on glycemic control remain unclear. The aim of this study was to modify the IMB model to explore the effects of self‐management on glycemic control in T2DM patients in Shanghai, China. Methods: A cross‐sectional study was conducted on participants recruited using a convenience sampling method between June and August 2015 in three tertiary hospitals and four community health service centers; 796 participants meeting the inclusion criteria (age ≥18 years and a diagnosis of T2DM) completed a questionnaire and blood test for glycemic control. Structural equation models were used to test the IMB framework. Results: The modified model demonstrated an acceptable fit of the data. Paths from information to self‐management behaviors (β = 0.119, P = 0.001) and HbA1c (β = −0.140, P < 0.001), from motivation to behavioral skills (β = 0.670, P < 0.001), from behavioral skills to self‐management behaviors (β = 0.562, P < 0.001), and from self‐management behaviors to HbA1c (β = −0.343, P < 0.001) were all significant and in the predicted direction. Information and motivation varied with each other ( r = 0.350, P < 0.001). Conclusions: Glycemic control can be incorporated into the IMB model. The utility of the modified model in the study population is validated. Type 2 diabetes mellitus patients with poor control of glucose levels may be a better target population for application of the modified IMB model. Abstract : Highlights Glycemic control can be incorporated into the information–motivation–behavioral skills (IMB) model. The utility of the modified IMB model in type 2 diabetes mellitus patients in Shanghai, China, is validated. Type 2 diabetes mellitus patients with poor glycemic control may be a better target population than patients with good glycemic control for application of the modified IMB model.